State-wide implementation of edTPA in preparation for high-stakes testing: A mixed-methods study of the concerns of edTPA coordinators - Many, Joyce E.; Bhatnagar, Ruchi; Tanguay, Carla; Favors-Welch, Shaneeka; Thomas, Clarice; Cannon, Susan Ophelia; Ogletree, Tamra; Kim, Jihye; Howrey, Shannon; An, Sohyun; Kurz, Karen; Wilson, Judi (Education Policy Analysis Archives, 2019)
This study examined the implementation of high-stakes adoption of edTPA® in one state in the year prior to consequential use of edTPA scores for teacher licensure. Using a mixed methods design, we investigated concerns of coordinators who were responsible for edTPA implementation in their institutions. We utilized the Concerns Based Adoption Model (CBAM) to understand edTPA coordinators’ Stages of Concern, the nature of the challenges they faced, and the professional development opportunities that alleviated their concerns. Based on the CBAM survey, the most common Stage of Concernfor edTPA coordinators was Management.Coordinators’ interviews revealed the nature of their concerns at different stages and how the size of their institution and supportive resources at particular times may have played a crucial role in shaping the edTPA roll-out in their institutions. The use of the CBAM framework enabled edTPA coordinators (a) to understand their own concerns about the high-stakes policy, (b) to articulate the complexities involved in implementing edTPA initiatives, and (c) to underscore the importance of relating concerns to appropriate professional development opportunities and support for themselves as well as their faculty.